(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background & Objective Sacrococcygeal teratoma is the most common Congenital neonatal tumour. Sacrococcygeal teratoma (SCT) can be detected by ultrasound in early foetal life. Currently, prenatal ultrasonography enables examination of tumours, but it does not always provide all the needed data. The purpose of this study was to highlight the most important features of SCTs detected by foetal MRI adding to ultrasound information. Case series Between 2015 and 2020, Four cases of sacrococcygeal teratomas were either diagnosed in our hospital or referred to our hospital for foetal magnetic resonance imaging. Antenatal ultrasound screening was done at our hospital preceding foetal MRI examination. As surgery is the mainstay for management of SCT, the required data before surgery include tumour dimensions, content, mass effect, and type of sacrococcygeal teratoma according to The American Academy of Paediatrics’ surgical section (APPSS). Foetal magnetic resonance imaging (MRI) was ideal for tumour classification using the aforementioned criteria. MRI better characterizes tumour content, its extent and relation to surrounding structures compared to ultrasound and enables a precise structural assessment of the central nervous system. Conclusions Foetal MRI is very informative in the prenatal diagnosis of SCTs as it overcomes the limitations of obstetric ultrasound providing additional data.